2022
DOI: 10.3390/su142215027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Primary Key Stratum on Surface Subsidence during Longwall Mining

Abstract: The surface subsidence caused by mining influences the mine environment and construction safety. In this paper, strata movement and surface subsidence were combined. Based on elasticity and Winkler theory, a prediction method of surface subsidence was established with the primary key stratum as the research object. Using the Tingnan Coal Mine as an example, the mining subsidence of the second panel was predicted. Comparing the predicted results with the measured results, the causes of errors were analyzed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(57 reference statements)
1
0
0
Order By: Relevance
“…14 . Compared with the actual measured value, the predictions are relatively smaller, which are basically consistent with previous findings from similar studies 52 54 .
Figure 13 Post-mining ground surface fracture development (This photo is taken by Qinggang Lu at the subsidence area of 11701working face).
…”
Section: Discussionsupporting
confidence: 90%
“…14 . Compared with the actual measured value, the predictions are relatively smaller, which are basically consistent with previous findings from similar studies 52 54 .
Figure 13 Post-mining ground surface fracture development (This photo is taken by Qinggang Lu at the subsidence area of 11701working face).
…”
Section: Discussionsupporting
confidence: 90%
“…practice has shown that a relatively thick and hard rock layer above the coal seam roof serves as the main carrier of the overlying strata load, controlling the transfer and movement of loads between different rock layers. This layer is referred to as the key stratum [34][35][36] . Determining the number and position of key stratum is of significant importance for studying the structure and fracture characteristics of overlying strata.…”
Section: Engineering Backgroundmentioning
confidence: 99%